PENEGAKAN HUKUM OLEH APARAT KEPOLISIAN RESOR KOTA PADANG TERHADAP TINDAK PIDANA KEKERASAN YANG MENYEBABKAN KEMATIAN DALAM TAWURAN PELAJAR - Rafifa, Dhiyaul Okasha; Danil, Elwi; Yoserwan, Yoserwan (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
One form of delinquency that often occurs is student brawls, which are mass fights between groups of students. This phenomenon is increasingly concerning because it results in many injuries and fatalities. In the context of Indonesian law, the act of brawling is regulated in Article 170 and Article 358 of the Criminal Code, which provides criminal penalties for those involved in group violence. The research method used is empirical juridical by examining literature material first followed by interviews. Then, the data obtained is analyzed qualitatively with the nature of analytical descriptive research. The results of the discussion show that law enforcement against criminal acts of brawl by children has been enforced properly in accordance with the applicable criminal procedure law while still taking into account the rights and obligations of children. However, in its law enforcement, the Padang City Police Force experienced obstacles caused by several factors including statutory factors, law enforcement factors, facilities and infrastructure factors, community factors, and cultural factors. It is hoped that the government will make regulations that specifically regulate student brawls in Padang City and for the community, especially parents, to carry out maximum supervision of their children not to brawl. Keywords: Law Enforcement, Violent Crime, Brawl, Padang City Police Force.